Prediction of waterlogging using Digital Elevation Model and GIS - Pattanaaik, S K; Singh, O P; Singh, D K; Sahoo, R N (Journal of Agricultural Engineering, 2007)
Waterlogging is common in irrigated areas of Western Yamuna Canal command covering Gohana sub-division of Sonepat district of Haryana state. Probable flood water level indicating the degree of waterlogging was predicted by using digital elevation model (DEM) as the base and Geographic Information System (ILWIS Academic 3.0) for anaiysis. For different levels of probable flooding the percentage area that would be submerged and the volume of water to be drained had been calculated for 20 cm interval in flood stages. In this DEM based study, the volume of water to be drained was calculated by multiplying the difference between the surface elevation and flood level with the area of each pixel. A discrepancy between the predicted and actual flood water levels was found out and was attributed to either or both of the slope of the flowing water and ingress of floodwater from the neighboring areas, which were not considered in the present study. The developed methodology will be useful in designing drainage systems in command areas, which are inundated at times due to flooding.